Binderless grinding wheel for failure analysis of silicon die on I. C chips - 423577 Woon, Keng Soon (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering(Manufacturing) - Universiti Teknologi Malaysia, 2003